Australian parents' experiences of owning an autism assistance dog. (29th March 2022) - Appleby, Rebecca; Wright, Shelley; Williams, Lindy; Stanley, Mandy
Abstract: Autism assistance dogs (AADs) increase safety for children with autism and their families. Autism assistance dogs can also decrease familial stress and the isolation which families may experience due to fear for their child's safety and judgement from others within the community. Currently there is a paucity of literature on parents' experiences of AADs. Therefore, this study aimed to develop a rich understanding of parents' experiences of owning an AAD. A mixed methods design was utilised, with a qualitative descriptive design and the use of occupational mapping. Eight families were recruited through an Australian AAD programme and participated in semi‐structured in‐depth interviews throughout 2017. The interviews were analysed thematically. Mobility in the community before and after introduction of the dog was measured using occupational mapping. Families plotted on Google Map printouts the places they frequented before and after placement of their dog. Five major themes emerged from the analysis of the interviews: freedom through restraint; expanding our world; a calming/sensory tool (AAD); "at the end of the day they're dogs"; and, friendship and personal growth. The occupational maps demonstrated a median increase of 8.5 more places and 20.50 km further travelled from home after having the dog for over a year. Families with an AAD experienced an expanded world for the child and their family. Families experienced freedom in the places they could go, decreased isolation due to the safety which the dog provides. Occupational mapping supported the qualitative data, showing increased mobility and decreased isolation of the family. The paradox of freedom through restraint is a new and key finding which requires further exploration. The results provide support for funding and increased awareness of AAD programmes. Future longitudinal comparative studies are needed to explore the long‐term impact of AADs on the child and family.